Participatory conservation in the Semliro Traditional Village, Rahtawu Village, as an effort to preserve culture, environment, and land - Findayani, Aprillia; Ramdani, Rahmi; Azzahrah, Octavia; Kirani, Nabila Salsa (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The beauty of a Rahtawu Village certainly poses a threat from the are increasingly a rapid human activity to meet life's needs. The Dukuh Semliro community formed an effort to preserve the nature of Mount Muria, namely by building the Semliro Traditional Village. The aim of this research is to find out the role of participatory conservation carried out by the Semliro Traditional Village in an effort to preserve its ancestral heritage with efforts from cultural, environmental, and land acquisition aspects. Methods: The method applied is descriptive-qualitative, with the research object being the Semliro Traditional Village in Rahtawu Village, Gebog District, Kudus Regency, Central Java. Data were obtained through direct observation in the field and a literature study. Findings: The research results show that Semliro Traditional Village is an extension of efforts to preserve culture, environment, and land in Kudus Regency, especially Rahtawu Village. The level of participation of the Semliro Traditional Village community is quite low; this is also followed by the still low level of activity or behavior of the traditional community in terms of conserving their agricultural land resources. Conclusion: The Rahtawu Village community is a making efforts to preserve the Muria forest by enforcing norms in cultural aspects. Participatory conservation needs to be encouraged to restore environmental degradation that occurred in Rahtawu Village through Proklim (the Climate Village Program) and the formation of traditional villages. The policy regarding restrictions regarding land ownership for residents outside Rahtawu is expected to be able to minimize the negative impacts of massive development and support the potential of the tourism sector in Rahtawu Village.